Identifikasi Kesulitan Guru Matematika Dalam Pelaksanaan Pembelajaran Daring di Masa Pandemi Covid-19 - Ridhatul Husna; Yenita Roza; Maimunah Maimunah (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This study aims to identify the difficulties of mathematics teachers in carrying out their roles as teachers in online learning from the aspect of teachers as learning resources, demonstrators, motivators, managers, and evaluators. This research method is descriptive qualitative. The subjects were 25 SMA/MA mathematics teachers in Kabupaten Kuantan Singingi Riau Province. The data collection technique used an instrument in the form of a questionnaire. Data were analyzed using descriptive statistics. Based on the research results of the five indicators of the teacher's role, teachers have difficulty, especially in carrying out their role as demonstrators 62%, roles as motivators 50%, and roles as evaluators 50%.